East Coast fever (ECF)-2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Jaribu Sultan, veterinary specialist for FARM-Africa in northern Tanzania. The interview focuses on protecting animals by dipping and vaccination.